REDUCING NATIVE LANGUAGE INTERFERENCE IN ENGLISH TEACHING WRITING USING GRAMMARLY: A CASE STUDY - Muhammad syarofil Umam; Khoiriyah; Dewi Nurul Qomariyah; Ahmad Ridho Rojabi (Indonesian EFL Journal, 2026)
Native language (L1) interference continues to pose a significant challenge in English as a Foreign Language (EFL) classrooms, frequently resulting in systematic writing errors. Despite its prevalence, L1 interference among senior high school students, especially in relation to automated writing tools, has received limited scholarly attention. This qualitative case study investigates L1 interference patterns among students with Javanese, Madurese, and Balinese linguistic backgrounds and evaluates the effectiveness of Grammarly in reducing these errors. Data were gathered through classroom observations, teacher interviews, and analysis of students' argumentative essays, and subsequently analyzed using a systematic coding-category-theme approach. The findings indicate that L1 interference primarily manifests in syntactic, morphological, and lexical domains, largely due to a translation-oriented writing strategy. The use of Grammarly as a digital scaffold significantly improved students' grammatical awareness and facilitated independent revision. The results suggest that although digital tools enhance structural accuracy and learner autonomy, teacher intervention remains essential for addressing complex semantic challenges. This study provides pedagogical recommendations for integrating technology to reduce negative language transfer in diverse EFL contexts.